Perilaku Masyarakat dalam Memanfaatkan Air Sungai Siak sebagai Sumber Kehidupan dan Dampaknya terhadap Estetika serta Kesehatan Lingkungan di Wilayah Waterfront City Pekanbaru - Gusnan Suryadi; Thamrin Thamrin; Auda Murad (Universitas Riau, 2016)
This study aimed to analyze the behavior, the factors that influence and impact of the behavior of the public in using the Siak River as a place to meet the needs of life and routine activities on the health and aesthetic environment at waterfront city area Pekanbaru. Research has been conducted in Kampung Baru Senapelan District Pekanbaru from March 2013 until January 2014. This study was designed in accordance with method research in environmental psychology. Primary data collection using observation and interviews with informants is purposive sampling by participant observation researchers are passive. The results showed that the behavior of the public in using the Siak River as a place to meet the needs of life and activities of daily living (MCK) classified as bad as the Siak River sewage used as a domestic (household). Factors that affect people's behavior is that habit, low economic level and comfort. The impact of the people's behavior to public health such as the incidence of skin diseases and diarrhoea as a result of the increasing Escherichia coli bacteria. While the impact on the aesthetic appearance of the environment in the form of bad water, bad smells and visual pollution affecting river waters around waterfront city development in the city of Pekanbaru. Necessary to the arrangement of the Siak river environment clean and free of bad behavior of society through cooperation between the government and local communities in a sustainable manner.